Awareness of pharmacovigilance among future house officers; a study among first batch of final year medical students of UniSZA, Malaysia - Salwani, Ismail; Nor Iza, A.Rahman; Mainul, Haque (Association of Indian Pharmacist, 2015)
Drugs mainly intended to produce desired effects also lead to undesired adverse effects. Adverse Drug Reactions (ADRs) are frequently harmful and result in considerable morbidity and mortality. They also impose considerable economic burden on the person, society and the country. ADRs related health problems are known to contribute significantly to morbidity and mortality both in developed and developing countries. ADR reporting in Malaysia has been found to be low. It is probably due to lack of knowledge and reporting methods of ADRs both in University Hospital Doctors and General Practitioners. The reasons for underreporting of ADRs in Malaysia are not known. Considering all these facts this study was conducted to assess the knowledge, attitude and practice of final year Bachelor of Medicine and Bachelor of Surgery (MBBS) students of Universiti Sultan Zainal Abidin (UniSZA). This is a cross-sectional study conducted on Year V medical students of UniSZA of academic session 2013/2014. Universal sampling technique was used to select the sample. Out of 30 study population 77% were responded. Bulk (83%, 19) of the respondents were Malays, rest were Chinese (13%, 3), and Indians (5%, 1). Ninety-six percent of study participants know the term ADRs, but majority of them did not know the method of reporting ADRs. Eighty-seven percent of students during clinical clerkship observed ADRs. Current study findings suggested that there is need of educational interventions both in undergraduate course-work and also during houseman-ship.